2011
DOI: 10.1128/jb.05924-11
|View full text |Cite
|
Sign up to set email alerts
|

Peroxide Stimulon and Role of PerR in Group A Streptococcus

Abstract: We have characterized group A Streptococcus (GAS) genome-wide responses to hydrogen peroxide and assessed the role of the peroxide response regulator (PerR) in GAS under oxidative stress. Comparison of transcriptome changes elicited by peroxide in wild-type bacteria with those in a perR deletion mutant showed that 76 out of 237 peroxide-regulated genes are PerR dependent. Unlike the PerR-mediated upregulation of peroxidases and other peroxide stress defense mechanisms previously reported in Gram-positive speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 68 publications
4
60
0
Order By: Relevance
“…GAS encodes the regulator PerR, which acts to sense and coordinate the bacterial response to oxidative stress. Previous research examining the PerR regulon has shown that this regulator controls the direct detoxification of reactive oxygen species, mechanisms to repair ROSmediated damage, and a number of genes involved in metal homeostasis (6,33,34). Here, we provided evidence to suggest that the PerR-regulated GAS gene pmtA encodes an Fe(II) efflux pump that contributes to defense against reactive oxygen species.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…GAS encodes the regulator PerR, which acts to sense and coordinate the bacterial response to oxidative stress. Previous research examining the PerR regulon has shown that this regulator controls the direct detoxification of reactive oxygen species, mechanisms to repair ROSmediated damage, and a number of genes involved in metal homeostasis (6,33,34). Here, we provided evidence to suggest that the PerR-regulated GAS gene pmtA encodes an Fe(II) efflux pump that contributes to defense against reactive oxygen species.…”
Section: Discussionmentioning
confidence: 48%
“…A consensus per box, the regulatory element bound by PerR, is found immediately upstream of the pmtA gene (6,25,33). We therefore sought to determine whether pmtA is upregulated by hydrogen peroxide, consistent with PerR regulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A). We also determined the role of PolA1 in GAS adaptive defenses against peroxide damage by preincubating cultures at sublethal H 2 O 2 levels recently reported to elicit genome-wide responses in GAS (22) prior to lethal peroxide challenge. Following a 30-min preadaptation in 0.5 mM H 2 O 2 , wild-type bacteria could withstand a subsequent 60-min challenge with 10 mM H 2 O 2 , retaining over 80% viability.…”
Section: Perr Is Expressed From a Five-gene Operon In Gasmentioning
confidence: 99%
“…In its reduced ferrous-ionbound form, PerR represses the expression of several products, including two peroxidases (KatA and AhpC/AhpF), the iron/ DNA-binding ferritin-like MrgA, and a zinc uptake protein (ZosA), and heme biosynthesis, whereas in the presence of peroxide, ferrous-ion oxidation leads to OH ⅐ , which oxidizes and inactivates PerR, thereby allowing derepression of peroxide stress defenses (20,21). Recent characterization of wild-type (WT) and perR mutant group A Streptococcus (GAS) transcriptome changes elicited by H 2 O 2 showed PerR-dependent downregulation of DNA and protein metabolism, but no upregulation of any known peroxidases or MrgA (22). Moreover, comparison of transcriptomes obtained from the same two wild-type and mutant GAS strains in the absence of H 2 O 2 indicated control by PerR of a different set of genes that included a strongly repressed putative metal transporter (23,24).…”
mentioning
confidence: 99%